2015
DOI: 10.1519/jsc.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Size and Physical Characteristics of South African Under-20 Rugby Union Players Over a 13-Year Period

Abstract: This study compared changes in the body size and physical characteristics of South African under-20 rugby union players over a 13-year period. A total of 453 South African under-20 players (forwards: n = 256 and backs: n = 197) underwent measurements of body mass, stature, muscular strength, endurance, and 10- and 40-m sprint times. A 2-way analysis of variance was used to determine significant differences for the main effects of position (forwards vs. backs) and time (1998-2010). The pooled data showed that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 26 publications
7
80
0
Order By: Relevance
“…Age-grade RU players' height and body mass are greater for older players [62] and are higher in forwards than backs [63]. The height and body mass of U21 English players [62] appear similar to those reported for South African U20 players [59] and greater than those reported in U19 Portuguese forwards and backs [58]. Only one study has reported the anthropometric characteristics of players below 16 years old considering height, mass and maturity status in 14-17-yearold English players [64] and shows youth RU players were above the seventy-fifth and ninetieth reference percentiles for height and mass, respectively.…”
Section: Anthropometricssupporting
confidence: 61%
See 1 more Smart Citation
“…Age-grade RU players' height and body mass are greater for older players [62] and are higher in forwards than backs [63]. The height and body mass of U21 English players [62] appear similar to those reported for South African U20 players [59] and greater than those reported in U19 Portuguese forwards and backs [58]. Only one study has reported the anthropometric characteristics of players below 16 years old considering height, mass and maturity status in 14-17-yearold English players [64] and shows youth RU players were above the seventy-fifth and ninetieth reference percentiles for height and mass, respectively.…”
Section: Anthropometricssupporting
confidence: 61%
“…Due to the physical demands of RU, players require highly developed physical qualities, including anthropometry, body composition, linear and change of direction speed, high-intensity running ability, strength and power [6]. Previous research has presented the physical qualities of senior [53][54][55][56] and youth [53,[57][58][59] RU players across multiple ages, standards and positions. Specific to male age-grade RU players within England, ten studies [46,49,[60][61][62][63][64][65][66][67] have presented data across various physical qualities making comparisons between age, position and playing level.…”
Section: Physical Qualitiesmentioning
confidence: 99%
“…U20s internationals). With the exception of the work by Lombard et al, [18] on the 10 year physical evolution of South African U20s players, the research of Barr and colleagues [19] reporting speed characteristics of U20s players from a nation outside of the top 10 (i.e. tier 2), and movement characteristics in U20 players However, currently no literature exists on how these demands map with those of their senior counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a historical evolution of both senior and junior rugby players from a physical perspective [18, 21] with the rate of increase in body mass particularly large in the last 30–40 years [21]. For example, South African U20s players have increased in height (~2.8%), weight (~14%), strength (~51%), muscular endurance (~50%), and improved speed times over 10m (~7%) and 40m (~4%) but have not improved aerobic performance over a 13 year period [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation